2022
DOI: 10.3389/fpls.2022.871021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar With Inorganic and Organic Fertilizers on Agronomic Traits and Nutrient Absorption of Soybean and Fertility and Microbes in Purple Soil

Abstract: Biochar is a kind of organic matter that can be added into the soil as a soil amendment to improve its quality. What are the effects of using biochar on purple soil and soybeans? Can the use of biochar reduce the use of fertilizers? This is our concern. Therefore, we carried out this study. The objectives of our study were to evaluate the effects of biochar, inorganic and organic fertilizer application on plant growth, chlorophyll content, photosynthetic gas exchange, and yield of soybean as well as fertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…It was recorded by several studies that microalgae extracts, such as polysaccharides, enhanced crop productivity (Vacca et al, 2004 ; Obertello et al, 2010 ; Ding et al, 2018 ; Jagodzik et al, 2018 ), and this is likely responsible for the enhancing potential of HVPE and WRB as shown in our results. Interestingly, our findings on the vegetative parameters were consistent with previous findings which proved that organic material had a beneficial effect on crops such as rice and soybean (Wang et al, 2012 , 2016 ; Liu et al, 2022 ). Also, the impacts of HVPE and WRB were felt on the chlorophyll content in bell pepper plants through the entire growth stage.…”
Section: Discussionsupporting
confidence: 92%
“…It was recorded by several studies that microalgae extracts, such as polysaccharides, enhanced crop productivity (Vacca et al, 2004 ; Obertello et al, 2010 ; Ding et al, 2018 ; Jagodzik et al, 2018 ), and this is likely responsible for the enhancing potential of HVPE and WRB as shown in our results. Interestingly, our findings on the vegetative parameters were consistent with previous findings which proved that organic material had a beneficial effect on crops such as rice and soybean (Wang et al, 2012 , 2016 ; Liu et al, 2022 ). Also, the impacts of HVPE and WRB were felt on the chlorophyll content in bell pepper plants through the entire growth stage.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that we found no significant variations in the plant physiological parameters (FPSII, NDVI), their relative increase in MF fertilized treatments (Figures 1C, D) confirms the direct dependence of chlorophyll content and photosynthesis on nutrient availability, especially nitrogen (Huang et al, 2004;Mu and Chen, 2021). This shows that the applied biochars were unable to cast any additional benefit on crop's physiological parameters, however, their combination with mineral fertilizers shows the potential to increase plant growth, as demonstrated also by other studies (Kizito et al, 2019;Li et al, 2020;Ndoung et al, 2021;Liu et al, 2022). The improved crop performance under combined application of biochars and mineral fertilizers could be due to the improved crop nutrient and water availability coming from fertilizer and the mechanisms of biochar on retention and exchange of these nutrients on biochar surfaces which lead consistent supply of nutrients to crops (Agbna et al, 2017;Singh et al, 2019b;Faloye et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Biochar alkalinity may stimulate the growth of Gram-negative and Gram-positive bacteria (Zimmermann et al, 2012;Osman et al, 2022). Sun et al (2012) observed the bacterial populations were more dynamic and active in biochar-treated soil than fungal populations under field conditions; this may be attributed to the biochar's higher surface area and biochar carbon (Liu et al, 2022). Moreover, pyrolysis temperature, biomass type, and carbon content strongly influence dehydrogenase activity, microbial habitats, N immobilization and mineralization (Ameloot et al, 2015).…”
Section: Effects On Soil Biological Attributesmentioning
confidence: 99%